Application of CRISPR-mediated genome engineering in cancer research. (28th February 2017) - Sayin, Volkan I.; Papagiannakopoulos, Thales
Highlights: In vitro modeling of genetic variants using CRISPR/Cas9. Somatic genome engineering with CRISPR/Cas9. CRISPR/Cas9-based effectors. CRISPR/Cas9-based genetic screens. Looking forward: Caveats and future applications of the CRISPR/Cas9 system in cancer biology. Abstract: Cancer is a multistep process that arises from a series of genetic and epigenetic events. With recent technological advances there has been a burst in genome sequencing and epigenetic studies revealing a plethora of alterations that may contribute to cancer. However, the great challenge for the cancer research community is the systematic functional characterization of these genetic and epigenetic events to assess their role in cancer initiation and progression. Recent advances in genome engineering using CRISPR/Cas9, an ancient bacterial immune-like system, have revolutionized cancer genetics. Here we highlight the breakthroughs in the effective use of these novel genome-editing techniques, and we discuss the challenges and potential applications of these tools for cancer biology.